Exploring the pharmacological mechanisms of icaritin against nasopharyngeal carcinoma via network pharmacology and experimental validation - Liu, Minglu; Hu, Tong; Gou, Wenfeng; Chang, Huajie; Li, Yanli; Li, Yiliang; Zuo, Daiying; Hou, Wenbin; Jiao, Shunchang (Frontiers in Pharmacology, 2022)
Background: Icaritin is a natural product with a wide range of anti-tumor effects. However, its anti-tumor mechanism has not been thoroughly investigated. This study combined network pharmacology with in vivo and in vitro experiments to investigate the inhibitory effect of icaritin on nasopharyngeal carcinoma and its underlying mechanism. Methods: MTT and clone formation assays were used to detect the effects of icaritin on the viability and proliferation of nasopharyngeal carcinoma cells, followed by the construction of a HONE1 xenograft tumor model to evaluate the in vivo anti-tumor efficacy of icaritin. A public database was used to predict potential targets, construct a protein-protein interaction (PPI) network, and perform gene enrichment and biological process analyses. Based on network pharmacological data, western blotting was performed to detect the expression of cell cycle-related proteins, and flow cytometry was performed to detect apoptosis, cell cycle distribution and intracellular reactive oxygen species (ROS) production. In addition, SA-β-Gal staining was performed to detect cellular senescence, and western blotting was performed to detect the expression of P53, P21, and other proteins to verify key signaling pathways. Results: Icaritin effectively inhibited the viability and proliferation of nasopharyngeal carcinoma cell lines and showed good anti-tumor activity against HONE1 nasopharyngeal carcinoma cells in vivo. Key protein targets, including AKT1, HSP90AA1, CDK4, CCND1, and EGFR, were screened using PPI network topology analysis. GO and KEGG analysis revealed that the cell cycle, p53 signaling, and cell senescence pathways may be the main regulatory pathways. Flow cytometry and western blot experiments showed that icaritin caused S-phase arrest and promoted an increase in ROS. SA-β-Gal staining showed that icaritin significantly induced cellular senescence, and western blotting revealed a significant increase in the expression of P53 and P21. Moreover, inhibition of ROS levels by N-Acetylcysteine (NAC) enhanced cell viability and decreased the proportion of cellular senescence. Conclusion: Comprehensive network pharmacological analysis and the results of in vivo and in vitro experiments showed that icaritin effectively inhibited the growth of nasopharyngeal carcinoma cells, promoted ROS production, induced cellular senescence, and inhibited tumor cells. The mechanism of action may be related to regulation of the P53/P21 signaling pathway.